Hong Kong Taxation : Law and Practice 2012-13 Edition - Lau, Ayesha Macpherson; Laird, Garry (Book collections on Project MUSE., 2013)
This book covers the major areas of Hong Kong taxation -- Property tax, Salaries tax, Profits Tax, Personal Assessment, and Stamp Duty. It explains the principles and practice of taxation law through relevant tax cases, Board of Review decisions, and numerous practical examples. The current edition includes the 2011-12 budget changes and latest developments in taxation. An added chapter focuses exclusively on international tax issues and a new section examines Hong Kong taxation issues for Mainland investors in Hong Kong. Experienced tax professionals at KPMG update this standard resource annually, an international network of member firms offering audit, tax, and advisory services.The text is written in a clear and concise manner, with technical jargon is kept to a minimum. Its strongest feature is its quick and easy-to-use index of significant court cases, Board of Review decisions, and relevant sections of the Inland Revenue Ordinance, Inland Revenue Rule, and Stamp Duty Ordinance.